IMPLEMENTASI TERAPI MUHASABAH DALAM MENINGKATKAN MOTIVASI BELAJAR SEORANG REMAJA SMA SURABAYA - Islamia, Adinda Rahma; Abd. Syakur (STAI Pelabuhan Ratu, 2025)
This article discusses the implementation of self-reflection therapy as an effort to increase the learning motivation of adolescents who experience a decline in learning enthusiasm due to family conflict, unstable emotional conditions, and peer influence. The choice of self-reflection is important because low learning motivation impacts achievement and discipline, while self-reflection as an Islamic technique has benefits in fostering self-awareness and improving learning behavior. This study uses a qualitative research method with a case study approach, with data collection through observation, in-depth interviews, and documentation, then analyzed using comparative analysis and synthesis by comparing the conditions of the client before and after therapy. The results of the study indicate that self-reflection therapy is effective in increasing intrinsic motivation, discipline, self-control, and more directed learning behavior, so that the client becomes more emotionally stable and responsible for their learning process.